Digital technologies as potentiating tools in the dissemination of information in museum spaces: Impact of the Covid-19 pandemic on museums - Felix da Silva, Letícia; Cardozo Padilha, Renata (Advanced Notes in Information Science, 2023)
This chapter seeks to discuss the digital humanities activity in the museological context, considering the importance of using digital technology tools for information dissemination in museum spaces and highlighting the period faced by the COVID-19 pandemic. The methodology used for the preparation of this chapter is defined as bibliographic and exploratory. Regarding the results obtained, it was possible to determine that using digital technology tools helps in cultural propagation from the informational dissemination of museological institutions in the virtual environment, which was indispensable during social isolation. In this sense, this chapter concludes the importance of using technological tools in the museological environment to reach various audiences without the interference of time/space.